Assessment of rewetting scenarios under varying climate conditions in a partially restored raised bog in Bavaria, Germany - Friedrich, Sebastian; Gerner, Alexander; Tarantik, Michael; Chiogna, Gabriele; Disse, Markus (Journal of Hydrology: Regional Studies, 2024)
Study region: Raised bog “Königsdorfer-Weidfilz”, Bavaria, Germany. Study focus: This study investigates effects of different rewetting scenarios on water levels in raised bog peat under varying climatic conditions. We apply physically-based models with high temporal and spatial resolutions to compare seasonal and annual water levels. The results were evaluated to determine the significance of these water level changes. Based on these water levels, a qualitative assessment was conducted to determine the percentage of areas that are more or less likely contributing to climate change through greenhouse gas emissions. New hydrological insights: Our study demonstrates the potential for investigating the rewetting of small peatland areas using high-resolution three-dimensional hydrological models. By utilizing a partially rewetted raised bog as a case study, we successfully modeled areas with different drainage states. Our results indicate that the areas rewetted in the respective scenarios behave similarly to the areas that have already been rewetted on site. Our study highlights that additional rewetting measures have a positive impact on reducing climate-active areas with low water levels in raised bogs. When combined with natural vegetation succession and changes in soil properties resulting from the formation of a new functional acrotelm layer after rewetting, these changes further enhance the effectiveness of the rewetting process. Although the influence of relevant dry periods after rewetting remains significant, our results suggest that the resilience of the peatland increases.
CRIS-Team Scopus Importer:2024-04-17
Keywords: Integrated hydrological model; Raised bog; Rewetting scenarios; Water level analysis